The role of acid sensing ion channels in the cardiovascular function - López-Ramírez, Omar; González-Garrido, Antonia (Frontiers in Physiology, 2023)
Acid Sensing Ion Channels (ASIC) are proton sensors involved in several physiological and pathophysiological functions including synaptic plasticity, sensory systems and nociception. ASIC channels have been ubiquitously localized in neurons and play a role in their excitability. Information about ASIC channels in cardiomyocyte function is limited. Evidence indicates that ASIC subunits are expressed in both, plasma membrane and intracellular compartments of mammalian cardiomyocytes, suggesting unrevealing functions in the cardiomyocyte physiology. ASIC channels are expressed in neurons of the peripheral nervous system including the nodose and dorsal root ganglia (DRG), both innervating the heart, where they play a dual role as mechanosensors and chemosensors. In baroreceptor neurons from nodose ganglia, mechanosensation is directly associated with ASIC2a channels for detection of changes in arterial pressure. ASIC channels expressed in DRG neurons have several roles in the cardiovascular function. First, ASIC2a/3 channel has been proposed as the molecular sensor of cardiac ischemic pain for its pH range activation, kinetics and the sustained current. Second, ASIC1a seems to have a critical role in ischemia-induced injury. And third, ASIC1a, 2 and 3 are part of the metabolic component of the exercise pressure reflex (EPR). This review consists of a summary of several reports about the role of ASIC channels in the cardiovascular system and its innervation.